Waste management of a wire production application through line production industry cleaner - Silva, Michele Salles da; Santos, Débora Aparecida da Silva; Silva, Fernanda Pereira; Berrêdo, Valéria Cristina Menezes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The production of cotton yarn and mixed (cotton + polyester) that supplies the textile industry generates large amount and variety of waste, which when managed badly can turn into a major environmental problem. An environmental management tool was chosen, the "Cleaner Production" (PML) to evaluate the management process of the waste produced by a local industry. This paper analyzes the management of waste generated by an industry with line yarn production activity by PML tool. The research is the study a case developed in a medium-sized industry with production line of activity, located in a city in the Mato Grosso state-MT, in November of 2014. Stages of production have been described industry and the production of waste in each stage, from a technical visit of the researchers,accompanied by one of the said industry managers. As a result was observed not using PML management tool for home industry, suggested getting your job to minimize the generation of waste, through the commitment of managers and correct training of employees through environmental awareness.